2014
DOI: 10.3788/col201412.111403
|View full text |Cite
|
Sign up to set email alerts
|

Stable multi-wavelength thulium-doped fiber laser based on all-fiber Mach–Zehnder interferometer

Abstract: We propose and experimentally demonstrate a multi-wavelength thulium-doped fiber (TDF) laser based on all-fiber Mach-Zehnder interferometer (MZI) at 1.9 mm. Here a segment of 4 m single-mode TDF is pumped by 1568 nm fiber laser for 2 mm band optical gain. The MZI includes two cascaded 3 dB coupler. A segment of 3.5 m long un-pumped polarization-maintaining TDF and polarization controller (PC) are joined in the ring cavity to suppress the mode competition. Multi-wavelength lasers at 1.9 mm with wavelength numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…To switch the wavelength, wavelength-selection and competitioninhibition mechanisms are needed. The wavelength can be selected with filters, such as the Mach-Zehnder interferometer [17] , cascaded Sagnac loop [18] , fiber-based Lyot filter [19] , micro fiber-optic Fabry-Perot interferometer [20] , few-mode fiber-based interferometer [21][22][23] and fiber Bragg grating (FBG) filters [7,24] . In particular, the FBG filter has been a good choice due to its simple structure, small size, and flexible tunability [25][26][27] .…”
Section: Introductionmentioning
confidence: 99%
“…To switch the wavelength, wavelength-selection and competitioninhibition mechanisms are needed. The wavelength can be selected with filters, such as the Mach-Zehnder interferometer [17] , cascaded Sagnac loop [18] , fiber-based Lyot filter [19] , micro fiber-optic Fabry-Perot interferometer [20] , few-mode fiber-based interferometer [21][22][23] and fiber Bragg grating (FBG) filters [7,24] . In particular, the FBG filter has been a good choice due to its simple structure, small size, and flexible tunability [25][26][27] .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, how to achieve high stability, narrow linewidth, and wavelength flexibility with rapid wavelength tuning or selection are the key to successful deployment for thulium-doped fibers lasers (TDFL). The current tuning devices include fiber Bragg grating (FBG) [9][10][11][12][13], F-P cavity [14][15][16], Sagnac fiber ring [17,18], Lyot filter [19][20][21], Mach-Zehnder interferometer [22][23][24], liquid crystal spatial light modulator [25], digital micromirror device (DMD) [26][27][28], and so on. Up to now, a DMD chip as a semiconductor-based addressable micromirror array has drawn considerable attention due to its flexible and fast filtering functionality in optical switching, interconnecting, and lasers.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the wavelength-tunable TDFL could be realized by utilizing fiber Bragg gratings (FBGs) [11,12], volume Bragg gratings (VBGs) [13,14], diffraction gratings [15] Mach-Zehnder interferometer [16] and Fabry-Perot (F-P) filter [17]. In 2014, Liu et al reported a tunable dualwavelength TDFL based on a high birefringence fiber Bragg grating (HB-FBG).…”
Section: Introductionmentioning
confidence: 99%